HARMONI DALAM GERAK, MENGUNGKAPKAN MAKNA TARIAN HEDUNG ADONARA - Klara D. Kewa Lamalelang; Hiwa Wonda (STKIP Subang, 2025)
Hedung Dance is a traditional dance of the Lamaholot people in Adonara Island, East Nusa Tenggara, which holds historical, philosophical, and spiritual values. This study aims to explore the symbolic meaning, cultural values, and social functions of the Hedung Dance within the Adonara community. This research adopts a literature review method by analyzing books, academic journals, cultural articles, and local documents. The findings show that Hedung Dance is not merely a form of entertainment but also serves as a medium of spiritual communication, a symbol of unity, and a representation of bravery. The dance elementsmovements, music, costumes, and formations reflect a harmonious relationship between humans, nature, and ancestors. Thus, preserving this dance is essential to maintaining local cultural identity in the face of globalization.